Quality of life among menopausal women – is it still an enigma? - Majumdar, Somak; Dasgupta, Aparajita (Indian Journal of Community Health, 2016)
Background: Menopause is a universal event in a women’s life occurring in the middle period causing a variety of physical, vasomotor, psychological and sexual symptoms. These symptoms generally tend to usually go underreported. Aims & Objectives: To find out the quality of life among the menopausal women and associations of menopausal symptom domains with their socio-demographic parameters. Material & Methods: The present cross-sectional study was undertaken in a slum of Chetla, Kolkata. Response to each question in the MENQOL questionnaire, was assigned a score and the composite scores assessed the quality of life and impact of menopause among the study population. Results: Out of a total of 100 women, psychosocial symptoms were the most prevalent with anxiety, loss of memory and nervousness to be 76%. Occurrence of vasomotor symptoms was average with 55% of them reporting hot flashes and 40% reporting sweating. Physical symptoms were highly variable and sexual symptoms were not prevalent. Psychosocial symptoms had the most associations and religion, literacy, marital status, and abortion all had significant associations. Conclusion: It is indeed imperative that quality of life among menopausal women is affected by the symptoms of menopause and measures should be taken for mitigation of the same